2020
DOI: 10.1111/jmi.12927
|View full text |Cite
|
Sign up to set email alerts
|

Anion intercalated graphite: a combined electrochemical and tribological investigation by in situ AFM

Abstract: The intercalation of graphite by electrochemical methods is an efficient strategy to produce massive graphene flakes. In fact, when graphite is biased inside an acidic solution, anions enter inside the stratified structure of the electrode and reduce the layer-to-layer interaction. Consequently, a gentle sonication is sufficient to disperse the graphene flakes inside the electrolyte. In view of an optimisation of the production protocol, a detailed analysis of the intercalation mechanism at the molecular lengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…By means of EC-AFM and EC-STM coupled with cyclic voltammetry it has been also demonstrated that the early stages of anion intercalation are highly affected by a number of factors like surface faceting, step erosion, terrace damages, and nanoprotrusions. [97,98] From these studied it emerged that AFM resulted particularly sensitive in detecting the very early stage of intercalation. Once SEI is formed, the subsequent process of intercalation/deintercalation of lithium cations within the graphite layers is basically reversible.…”
Section: Ec-afm For the Analysis Of Libs Anodesmentioning
confidence: 99%
“…By means of EC-AFM and EC-STM coupled with cyclic voltammetry it has been also demonstrated that the early stages of anion intercalation are highly affected by a number of factors like surface faceting, step erosion, terrace damages, and nanoprotrusions. [97,98] From these studied it emerged that AFM resulted particularly sensitive in detecting the very early stage of intercalation. Once SEI is formed, the subsequent process of intercalation/deintercalation of lithium cations within the graphite layers is basically reversible.…”
Section: Ec-afm For the Analysis Of Libs Anodesmentioning
confidence: 99%
“…The present special issue comprises 10 papers, showing to the interested reader a wide variety of excellent work presented at the extended version of the StSPM workshop. Atomic Force Microscopy (AFM) was employed in the graphene framework, aiming to study the exfoliation of large flakes of this 2D material from graphite via electrochemical approaches characterised by in situ AFM, 4 and to characterise graphene deposition on silicon surfaces that were nanostructured by lowenergy oxygen ion irradiation. 6 AFM was employed by Canino et al 5 to evaluate the surface roughness and image the surface morphology of Al + ion implantation of hexagonal silicon carbide (4H-SiC), a key process in the realisation of power electronic devices.…”
mentioning
confidence: 99%